Impact of using B100 Biodiesel in Ship Engines - Kamolpatara Limratana; Sompong Pichetpinyo; Tanet Aroonsrisopon; Samai Jai-in (Agriculture and Natural Resources, 2010)
The usability of fuel for ship engines produced from palm oil was investigated as pure biodiesel (B100) and with a 5% blend of petroleum diesel fuel (B5) in a 441 kW main engine and a 177 kW diesel generator. The objectives were to investigate the effects of B100 on the brake specific fuel consumption (BSFC), brake thermal efficiency (ηtb), exhaust gas temperature (EGT) and carbon monoxide (CO) content in the exhaust gas and the effect on engine parts, compared with B5. All experiments were undertaken in the Naval Dockyard Department. The main engine and diesel generator were worked at 60 and 40% engine load, respectively. The average values of BSFC for B100 when used with the main engine were higher than for B5 and in the range 16.14- 26.00%, because B100 had a lower heating value and higher density compared with B5. The impact on emissions was based on the average values of CO produced by B100 when used in the main engine at a speed of 800 rpm and was 11.09% higher than for B5. However, at speeds of 1100 and 1400 rpm, B100 produced 4.84% and 27.25% less CO than B5, respectively, because B100 had a higher flash point and oxygen content compared with B5. In addition, corrosion from soot and deposits using B100 should be comparable to those from using B5, if the water content does not exceed 0.05% by weight.